Use of Communication and Information Technologies (CIT) in Peruvian Amazon University - Rios Ramirez, Roger Ricardo; Torres García, Luis Enrique; Meléndez Aspajo, Jaime Educardo; Fuchs Ojanama, Mary Ysabel (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2016)
The objective was to determine the characteristics of use communication and information technologies by teachers in professional work in a Peruvian amazon university. Material and methods: it was applied a instrument with items multiplechoice answers to measured the dimensions of profile, competence in use of communication and information technologies, academic useand affective vision to a random sample of 39 academics with different job training. The study was non-experimental, descriptive transversal. Results and conclusions: It was found that the highest percentage of teachers whown unfavorable results in the profile dimension of implementation and competence in the use of communication and information technologies, without equipment, deficient internet access and deficient skills to the use software in the daily work; while the affective vision show the favorable results.